2019
DOI: 10.3390/nano9111638
|View full text |Cite
|
Sign up to set email alerts
|

V3S4 Nanosheets Anchored on N, S Co-Doped Graphene with Pseudocapacitive Effect for Fast and Durable Lithium Storage

Abstract: Construction of a suitable hybrid structure has been considered an important approach to address the defects of metal sulfide anode materials. V3S4 nanosheets anchored on an N, S co-coped graphene (VS/NSG) aerogel were successfully fabricated by an efficient self-assembled strategy. During the heat treatment process, decomposition, sulfuration and N, S co-doping occurred. This hybrid structure was not only endowed with an enhanced capability to buffer the volume expansion, but also improved electron conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Notably, apart from the four primary peaks, another two peaks observed at 521 and 513.6 eV in the V 2p spectrum originated from the V–N bond in the hybrid materials . Furthermore, in the N 1s spectrum (Figure b), the peak located at 397.1 eV is assigned to the V–N bond, confirming the formation of VN in VG-70 hybrids again . Moreover, the high-resolution N 1s spectrum of the PV sample is illustrated in Figure S8.…”
Section: Resultsmentioning
confidence: 73%
“…Notably, apart from the four primary peaks, another two peaks observed at 521 and 513.6 eV in the V 2p spectrum originated from the V–N bond in the hybrid materials . Furthermore, in the N 1s spectrum (Figure b), the peak located at 397.1 eV is assigned to the V–N bond, confirming the formation of VN in VG-70 hybrids again . Moreover, the high-resolution N 1s spectrum of the PV sample is illustrated in Figure S8.…”
Section: Resultsmentioning
confidence: 73%
“…Moreover, the Tyndall effect can be clearly observed (Fig. S1c), indicating the formation of relatively thin, semiconducting nanosheets [29].…”
Section: Resultsmentioning
confidence: 94%
“…To date, two charge storage mechanisms of the diffusion-controlled intercalation/alloying/conversion process and the capacitance-controlled pseudocapacitive process are involved in various electrode materials for LIBs [23,43,58]. The power-law relationship between the measured current (i) and sweep rates (v) is generally expressed as Equation (5), where a and b are adjustable parameters [1,43,57,59]. The b values could be determined by slopes of log (v) − log (i) plots, and two typical b values of 1 and 0.5 indicated that the electrode was dominated by capacitive behaviors and diffusive behaviors, respectively [45,54,57].…”
Section: Resultsmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have attracted extensive attention in the energy storage field, owing to their high energy density, long lifespan, and low self-discharge properties [1][2][3][4][5]. However, present LIB systems based on carbon as anode and lithium metal oxides as cathode with low energy densities cannot satisfy the ever-growing energy demands for electronic devices [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%